Un Maestro per le giovani generazioni di studiosi di diritto ecclesiastico e di diritto ecclesiale, che si pongono domande più che offrire risposte (a proposito della raccolta di saggi, Lo spirito del diritto ecclesiale. Scritti scelti di R. Bertolino) (Stato, Chiese e pluralismo confessionale, 2022)
A leading guide for the new generations of Ecclesiastical and Canon Law scholars, the ones who got questions instead of offering answersABDTRACT: These brief notes just pretend to suggest some issues concerning a deepened anthology of essays written by an influential scholar, presented and collected by his colleagues of different approaches and generations. It definitely means to underline peculiar and still not completely explored issues in both Ecclesiastical and Canon Law: the liberty of conscience and the importance of religious freedom in defending fundamental human rights, the scientific purpose to investigate and analyse the still ongoing relevance of a renewed "Church" for a changing world. Rinaldo Bertolino's thoughts seem in this sense a gift to the youngest scholars, encouraging them to have more questions than answers.